DIGITAL DEVELOPMENT OF THE FOOD INDUSTRY IN MODERN ECONOMIC CONDITIONS (MMIT Proceedings, 2026)
The article examines the processes of digitalization and key development trends in the food industry under modern economic conditions. The author analyzes approaches to integrating digital technologies into traditional production and management models while maintaining enterprise competitiveness. The study addresses tools for stimulating technological innovations, challenges in financing digital projects, and the balance between short-term investment costs and long-term improvements in operational efficiency and sectoral sustainability.
Keywords: digitalization of the food industry; digital transformation; economic efficiency; technological innovations; supply chain management; competitiveness